Proceedings of the 30th ACM International Conference on Information &Amp; Knowledge Management 2021
DOI: 10.1145/3459637.3482000
|View full text |Cite
|
Sign up to set email alerts
|

DL-Traff: Survey and Benchmark of Deep Learning Models for Urban Traffic Prediction

Abstract: Nowadays, with the rapid development of IoT (Internet of Things) and CPS (Cyber-Physical Systems) technologies, big spatiotemporal data are being generated from mobile phones, car navigation systems, and traffic sensors. By leveraging state-of-the-art deep learning technologies on such data, urban traffic prediction has drawn a lot of attention in AI and Intelligent Transportation System community. The problem can be uniformly modeled with a 3D tensor (T, N, C), where T denotes the total time steps, N denotes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Compared to classical statistical methods, DNNs can better capture complex relationships in historical data while avoiding the need for hand-engineered features. Researchers have explored several approaches to represent traffic data, including temporal sequence modeling with recurrent neural networks [26], multidimensional matrix representations with convolutional neural networks [27], and graph neural networks [28]. DNN-based methods have been shown to deliver state-of-the-art results in various traffic-related tasks, such as ride-sharing [29], and travel planning [30].…”
Section: A Spatio-temporal Traffic Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to classical statistical methods, DNNs can better capture complex relationships in historical data while avoiding the need for hand-engineered features. Researchers have explored several approaches to represent traffic data, including temporal sequence modeling with recurrent neural networks [26], multidimensional matrix representations with convolutional neural networks [27], and graph neural networks [28]. DNN-based methods have been shown to deliver state-of-the-art results in various traffic-related tasks, such as ride-sharing [29], and travel planning [30].…”
Section: A Spatio-temporal Traffic Forecastingmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the development of advanced predictive models for traffic information using data-driven approaches such as deep neural networks (DNNs) [5]. Multiple studies have shown that traffic forecasting models based on DNNs outperform classical machine learning methods by a large margin [6], [7]. However, these models are typically trained to minimize the averaged prediction error, resulting in a considerable variation in performance across test samples [8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al came out with another paper [52] following the same graph design as [143], and presented a novel dynamic node-edge attention network to address the challenges from the demand generation and attraction perspectives. [39,111,112,200,301,308]. Due to the network nature of traffic flows, GNN fits the mold to model the interaction between placed sensors via GPS location or roads [114,174,288].…”
Section: 24mentioning
confidence: 99%
“…Deep learning on spatial and temporal data prediction. There are similar works with parking availability prediction such as predicting traffic density, pollution data, and the general availability of resources [11,18]. These works are categorized into grid-based and graph-based predictions [11].…”
Section: Related Workmentioning
confidence: 99%
“…There are similar works with parking availability prediction such as predicting traffic density, pollution data, and the general availability of resources [11,18]. These works are categorized into grid-based and graph-based predictions [11]. The grid-based prediction divides areas into equal-size grids and predicts the values for each grid (e.g., [34]).…”
Section: Related Workmentioning
confidence: 99%